Risk-taking behaviors of Hong Kong construction workers – A thematic study. (October 2017) - Man, S.S.; Chan, Alan H.S.; Wong, H.M.
Highlights: Factors that affect risk-taking behaviors of construction workers are identified. A grounded theory model for risk-taking behaviors of construction workers is proposed. Recommendations for reducing the risk-taking behaviors are provided. Abstract: A qualitative approach was employed to explore the attitudes and experiences of construction workers toward risk-taking behaviors and to identify the underlying reasons that may explain why construction workers take or do not take risks at work. Forty face-to-face individual interviews with construction workers were conducted. NVivo software was utilized to analyze the qualitative data. The data were categorized using grounded theory techniques and a three-stage coding approach. The grounded theory model that was established shows that risk-taking behavior was affected by factors in three contexts, namely, personal, behavioral, and environmental contexts. The findings of this study provide useful recommendations to reduce the risk-taking behaviors of construction workers, which include meeting the expectations of construction workers and optimizing benefits, such as convenience, work effectiveness, physical comfort, safety training that emphasizes on the unfavorable consequences of risk-taking behaviors, close safety supervision, safety fines, safety incentives, and time-sufficient work schedule.